Modeling of acoustic wave in transition region of tapered single mode fiber using Finite Element Method - Lee H.J.; Abdullah F.; Emami S.D.; Ismail A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Acoustic wave propagation; Acoustic wave velocity; Acoustic waves; Acoustics; Photonics; Single mode fibers; Cross sectional area; Fundamental mode propagation; Fundamental modes; Modeling of acoustic waves; Normalized frequencies; Taper Transition; Tapered single-mode fibers; Transition regions; Finite element method